Influence of molecular weight on dielectric properties and piezoelectric constant of poly(vinylidene fluoride) membranes obtained by electrospinning*) - Aminatul Sobirah, Zahari; Muhammad Hafiz, Mazwir; Izan Izwan, Misnon (Polimery, 2021)
A significant influence of the molecular weight on the dielectric properties and piezoelectric constant of poly(vinylidene fluoride) (PVDF) membranes obtained by electrospinning was demonstrated. Electrochemical impedance spectroscopy and d33 meter were used to evaluate dielectric properties and piezoelectric constant respectively. The presence of the β-phase was determined by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The membranes with the lowest molecular weight (180,000 g/mol) possessed the best dielectric properties. They also had the highest piezoelectric constant (21 pC/N) and dielectric constant (2.9 at 50 Hz) as well as the highest β-phase content (80.25%).